2020
DOI: 10.1515/cclm-2020-0411
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic profile and clinical implications of hematological parameters in hospitalized patients with coronavirus disease 2019

Abstract: AbstractObjectivesAs people across the world suffer from coronavirus disease 2019 (COVID-19), further studies are needed to facilitate evaluating the severity and prognosis of COVID-19 patients. In the study, we aimed to dissect the dynamic profile and clinical implications of hematological findings in hospitalized patients with COVID-19. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
70
2
9

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(94 citation statements)
references
References 27 publications
13
70
2
9
Order By: Relevance
“…It is possible that differences are also present across the complete data spectrum, even though they are not clearly visualized with PDF data. These results are in accordance to previous reports of changes in laboratory findings in COVID-19 infected patients, where conditions as leukopenia, lymphocytopenia and thrombopenia were reported (Fan et al, 2020;Ding et al, 2020). It is important to highlight that data analysis is not sufficient to characterize clinical hematological alterations in evaluated patients (when compared to demographic hematologic parameters data), once data was normalized for the evaluated sample set only.…”
Section: Discussionsupporting
confidence: 90%
“…It is possible that differences are also present across the complete data spectrum, even though they are not clearly visualized with PDF data. These results are in accordance to previous reports of changes in laboratory findings in COVID-19 infected patients, where conditions as leukopenia, lymphocytopenia and thrombopenia were reported (Fan et al, 2020;Ding et al, 2020). It is important to highlight that data analysis is not sufficient to characterize clinical hematological alterations in evaluated patients (when compared to demographic hematologic parameters data), once data was normalized for the evaluated sample set only.…”
Section: Discussionsupporting
confidence: 90%
“…In consistent with our study, Yang et al suggested NLR ≥3.3 as an indicator with clinical symptoms to change disease status from mild to severe disease [24]. NLR is reported to be used as an early indicator for the severe disease, similar to previous findings from a different patient population [24,25].…”
supporting
confidence: 92%
“…It is possible that differences are also present across the complete data spectrum, even though they are not clearly visualized with PDF data. These results are in accordance to previous reports of changes in laboratory findings in COVID-19 infected patients, where conditions as leukopenia, lymphocytopenia and thrombopenia were reported (Fan et al, 2020;Ding et al, 2020). It is important to highlight that data analysis is not sufficient to characterize clinical hematological alterations in evaluated patients (when compared to demographic hematologic parameters data), once data was normalized for the evaluated sample set only.…”
Section: /14supporting
confidence: 91%